The Middle East and Europe the power deficit - Roberson, B. A. (Barbara Allen) (Routledge, 1998)
The end of the Cold War and the creation of the European Union have had profound effects on Europe's relationship with the Middle East. The contributors explore the relationship & examine the colonial legacies & economic prospects for both regions.